Surface plasmon resonance biosensor for real-time detection of genetically modified organisms - Cheah, Yoke Kqueen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Application of surface plasmon resonance (SPR) biosensor in detection of genetically modifed organism (GMO) is demonstrated. A total of four biotinylated probes namely Tnosb, P35Sb, LECb and TSQb were successfully immobilized onto the SA chip. Results analysis indicated that the SPR system with the sensor chip immobilized with the Tnosb, P35Sb, LECb and TSQb biotinylated probes potentially detect complementary standard fragments as low as 1 nM. Biospecifc interaction analysis (BIA), employing surface plasmon resonance (SPR) and biosensor technologies provide easy, rapid and automatable approach in detection of GMOs. Short assay times, label free DNA hybridization reaction and no toxic compounds are required, i.e. ethidium bromide, and the reusability of the sensor surface are some of the factors that contribute to the general advantages of the surface plasmon resonance (SPR) biosensor system in detection of GMOs.